Reforma agrária e estrutura fundiária no Brasil: uma análise a partir do I Plano Nacional de Reforma Agrária - Fleury, Renato Ribeiro [UNESP] (2015)
This research aims to discuss land reform policy and its impact on land concentration in Brazil from 1985 to 2010. The work historically reconstructed the process of formation and evolution of the Brazilian agrarian structure, showing the permanence it the following constituent features: high land concentration, exclusion from access to land for poor farmers, conflict and violence in the countryside and difficulty of land regulation by public authorities. During the phase of modernization of Brazilian agriculture, which lasted from mid-1960 to 1985 rose substantially land intended for incorporation into agricultural areas. In the most recent period, identified from 1985, the year in which it was implemented the First National Plan for Agrarian Reform (PNRA I) in the country, were revived hopes to reverse the previous historical trends, and the volume of land intended for layers of landless workers or those with little land through land policy also rose sharply between 1985 and 2010. Given these effects seen in the rural sector, this study established a comparison of coming impacts of agricultural land policies and modernizing with the impacts of policies of Agrarian Reform (PNRA I and II PNRA), comparing the evolution of the area destined to agricultural land mediated by agricultural modernization (1960 to 1985) with the evolution of land area distributed by the rural settlements program (1985-2010) performed by plans agrarian reform of the New Republic. Thus, it was the reason why the effects on indicators of land concentration in Brazil are still very significant